INCIDENCE OF SEPTORIA (SEPTORIA GLYCINES H.) DISEASES IN SOYBEAN VARIETIES - Toshmetova, Feruza; Meyliyev, Akmal (Innovatsion texnologiyalar, 2024)
Considered one of the most widespread ancient crops in the world, soybeans are currently grown in 91 countries covering 118 million hectares. Main producers: USA 70-90 million tons, Argentina 50 million tons, China 20-40 million tons, India 6-7 million tons, Russia 7-8 million tons, but its yield is less than 1 million tons. In the United States, about 100 million tons of soybeans are grown per year, the sown area is 30.9 million hectares. Also in our country, the areas of recropping of legumes are increasingly expanding. On the one hand, this will strengthen the grain independence of our country, and on the other hand, it will provide an opportunity to re-sow crops on lands empty of grain and grow a rich harvest. Solving the problem of ensuring food security in the republic and providing the population with food with a high protein content is becoming especially relevant in modern world politics. One of the ways to effectively solve this problem is to increase the cultivation of soybeans, rich in valuable protein, as well as to increase the scale of production of its processed products. However, although the scale of soybean cultivation in the republic has increased in recent years, economic efficiency is not achieved due to insufficient yields. Because in the conditions of our republic, fungal diseases of soybeans have not been studied and it has not been proven that they harm yields. This article describes the definition of the development of fungal diseases of soybean and the effect of fungicides on them